The Fight Against Rheumatism is in its 70th Year - Hatice Bodur (Archives of Rheumatology, 2017)
Rheumatology is the area of specialty that works on the diagnosis and treatment of inflammatory, degenerative, mechanical, metabolic or hereditary diseases which affect various organs and systems, mainly the musculoskeletal one. A rheumatologist is a licensed specialist who was educated on rheumatology after having completed specialty in the area of either physical medicine and rehabilitation or internal diseases.(1) In our country, physical medicine and rehabilitation specialists deal intensively with the diagnosis, treatment, and rehabilitation of rheumatic diseases in addition to the rehabilitation of musculoskeletal and neurologic system. The main reason behind this practice is that, in the core syllabus of physical medicine and rehabilitation specialty, such education and skills occupy a highly important place. In order to correctly understand the present day and where we stand, we need to have a good knowledge of the past, how we got here, and the milestones in this particular field. Rheumatology takes its origins from the antiquity. While it has completed its development into a well-known field of expertise in the 20th century, the fastest advancements have occurred in the past 50 years. The milestones of modern rheumatic treatment are the use of glucocorticoids in the treatment of rheumatoid arthritis in 1948 and the use of methotrexate in the treatment of dermatomyositis in 1968. In 1970s, it has been shown that aspirin blocks prostaglandin E. The efficiency of anti- tumor necrosis factor treatment was demonstrated in 1993 for the first time, and medicines of this sort entered the market in 1999. Biologic agents modifying diseases commenced a new era.(2,3) The years 2000-2010 were declared as the Bone and Joint Decade by the World Health Organization. The main aim of this project, which was supported by the United Nations and many states, was to enhance the quality of life of those who have musculoskeletal diseases. This independent and non-profit event has increased awareness on the diagnosis and treatment of rheumatic diseases.(4) Rheumatology is a relatively recent area of science in Turkey, and in the world. As a sub-specialty, it has developed with the contribution of physicians from other main and sub-specialties. With the university reform of 1933 in Turkey, and the establishment of physical treatment branch thereof, under the leaderships of Prof. Dr. Osman Cevdet Çubukçu in Istanbul, and Prof. Dr. Nüzhet Şakir Dirisu in Ankara, the diagnosis and treatment of rheumatic diseases have commenced in the scientific sense.(5) The first association on rheumatology in Turkey is the Turkish League Against Rheumatism (TLAR). It was established in May 2nd 1947 in the Physical Treatment and Hydrology Institute of Ankara University School of Medicine with the efforts of Prof. Dr. Nüzhet Şakir Dirisu in order to reduce the burden of rheumatic diseases on the individuals and society and to encourage, improve, and support training and research on treatment, prevention of diseases, the rehabilitation of musculoskeletal diseases. With the Cabinet decision of July 22nd 1949 numbered 67, TLAR acquired the status of association with public utility. Its founding members with their then-titles are Prof. Dr. Rasim Adasal, Dr. Faik Akalın, Dr. Hikmet Irda, Prof. Dr. Erdal Avşar, and Prof. Dr. İ. Şevki Atasagun (Figure 1). TLAR was established in the same year as The European League Against Rheumatism (EULAR) and it became a member of EULAR in 1947. In 1959, TLAR organized the fourth EULAR Congress in Istanbul and it marks the first rheumatology congress in Turkey. To date, TLAR has been the representative of EULAR in Turkey.(5) <f1> Prof. Dr. Nüzhet Şakir Dirisu, Prof. Dr. Hami Kocaş, Prof. Dr. Tansu Karabay Arasıl, Prof. Dr. Mesut Birol Atay, Prof. Dr. Peyman Yalçın, Prof. Dr. Şebnem Ataman, and Prof. Dr. Ayşen Akıncı Tan are the academicians who have previously served as presidents of our association. In the 70th anniversary of TLAR, we commemorate the esteemed researchers who have contributed to the association in its establishment and beyond. The center of our association is located in Ankara, and it has branches in Afyon, Antalya, Aydın, Bursa, Diyarbakır, Elazığ, Erzurum, İstanbul (Anatolian and European sides), and Sivas. The second association in the same field, Society for Research and Education in Rheumatology, was established in 1993 by rheumatologists who are specialists of internal medicine. The association was renamed in 2012 as Rheumatology Society of Turkey. EULAR representation in Turkey has been carried on by the partnership of Rheumatology Society of Turkey and TLAR since 2014. They are also represented together in the platforms of The Turkish Medical Association and The European Union of Medical Specialist. The official journal of our association, ‘Acta Rheumatologica Turcica’, was first published in 1975, and was renamed as Turkish Journal of Rheumatology in 2010 and as Archives of Rheumatology in 2014. We are honored to celebrate the 70th anniversary of our association which has served considerably in the field of rheumatic diseases in our country, and which meticulously strives to uphold this mission. We aim to continue to serve, as we have done so to date, whilst maintaining our presence in this field.